2018
DOI: 10.3390/ijms19103035
|View full text |Cite
|
Sign up to set email alerts
|

Paired CRISPR/Cas9 Nickases Mediate Efficient Site-Specific Integration of F9 into rDNA Locus of Mouse ESCs

Abstract: Hemophilia B (HB) is an X-linked recessive bleeding disorder, caused by F9 gene deficiency. Gene therapy combined with the CRISPR/Cas9 technology offers a potential cure for hemophilia B. Now the Cas9 nickase (Cas9n) shows a great advantage in reducing off-target effect compared with wild-type Cas9. In this study, we found that in the multicopy ribosomal DNA (rDNA) locus, the homology directed recombination (HDR) efficiency induced by sgRNA-Cas9n was much higher than sgRNA-Cas9, meanwhile without off-target in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
(47 reference statements)
0
10
1
Order By: Relevance
“…Thus, this is the first report demonstrating that L755507 promotes HDR events in vivo. In contrast, we did not observe a significant increase in the that, unlike DNA DSB-dependent strategies using wild-type Cas9, the nicking-based approach via Cas9n prevented the activation of NHEJ in medaka as well as other organisms or cells (Gao et al, 2017;Murakami et al, 2020;Paulsen et al, 2017;Y. Wang et al, 2018).…”
Section: Discussioncontrasting
confidence: 81%
“…Thus, this is the first report demonstrating that L755507 promotes HDR events in vivo. In contrast, we did not observe a significant increase in the that, unlike DNA DSB-dependent strategies using wild-type Cas9, the nicking-based approach via Cas9n prevented the activation of NHEJ in medaka as well as other organisms or cells (Gao et al, 2017;Murakami et al, 2020;Paulsen et al, 2017;Y. Wang et al, 2018).…”
Section: Discussioncontrasting
confidence: 81%
“…The Cas9n D10A and Cas9n H840A are the variants of Cas9 containing a single amino acid substitution, which permit generation of site‐specific nicks on a gRNA complementary or non‐complementary DNA single strand, respectively. The Cas9n‐based approach has been reported to be available for the HDR‐mediated knock‐in in human or mouse cells and cattle, which contributed to circumvent unwanted NHEJ‐mediated gene disruptions (Gao et al., 2017; Paulsen et al., 2017; Wang et al., 2018). In medaka, several studies have reported the successful knock‐in mediated by wild‐type Cas9‐based approaches (Gutierrez‐Triana et al., 2018; Murakami et al., 2017; Watakabe et al., 2018); however, no studies have achieved DSBs‐free knock‐in with the Cas9n in medaka and other teleost fish.…”
Section: Introductionmentioning
confidence: 99%
“…The Cas9n-based approach has been reported to be available for the HDR-mediated knock-in in human or mouse cells and cattle, which contributed to circumvent unwanted NHEJ-mediated gene disruptions (Gao et al, 2017;Paulsen et al, 2017;Wang et al, 2018).…”
mentioning
confidence: 99%
“…nD10A has been used to generate paired DNA nicks and efficiently disrupts genes in Drosophila and cell culture (Gopalappa et al, 2018; Port et al, 2014). Nicks induced by nD10A promoted higher HDR rates than nH840A, where HDR was almost undetectable (Bothmer et al, 2017; Hyodo et al, 2020; Mali et al, 2013; Wang et al, 2021, 2018). Furthermore, nD10A can boost specificity while reducing off-target effects since it requires two gRNAs that target complementary DNA strands to either disrupt a gene function or trigger HDR.…”
Section: Introductionmentioning
confidence: 95%